Nanoindentation measurements of a highly oriented wurtzite-type boron nitride bulk crystal. (31st January 2017) - Deura, Momoko; Kutsukake, Kentaro; Ohno, Yutaka; Yonenaga, Ichiro; Taniguchi, Takashi
Abstract: We succeeded in synthesizing a bulk crystal of wurtzite-type boron nitride (w-BN) by the direct conversion method. The synthesized crystal was approximately 2 mm wide and 350 µm thick, and highly oriented to the c -axis. We performed nanoindentation measurements on the c -plane of the w-BN crystal at room temperature to evaluate the mechanical properties of w-BN. The hardness and Young's modulus of w-BN from the obtained curves were simultaneously determined to be 54 ± 2 and 860 ± 40 GPa, respectively. The underlying physical mechanism that dominates the mechanical properties of group-III nitride semiconductors is also examined.